Optimalisasi Biaya Dan Jarak Distribusi Pada Depot Air JAVAQUA Menggunakan Metode Transportasi Dan Metode Network. - Luthfi Fauzi Rahman; Luthfi Nur Rahman (Peneliti.net, 2021)
Operational Research (Operations Research or OR) seeks to determine the direction of the optimum action of a decision problem under limited resource restrictions. The term operating research is often associated almost exclusively with the use of mathematical techniques to model and analyze decision problems. Although mathematics and mathematical models are the core of OR, problem solving is not just the development and solving of mathematical models. Specifically, decision problems usually include important factors that are intangible and cannot be translated directly in the form of mathematical models. The most important of these factors is the presence of human elements in almost every decision environment. In fact, there have been reported decision situations where human influence has so much influence on decision problems that the solutions obtained from mathematical models are seen as impractical. Transportation Method is an operational research technique (operational research) that is very petrified in making decisions regarding the location of factories and warehouses. Network (network) is a system consisting of a series of stains (nodes) and activities (activity). Networks are born because of various needs such as: transportation, electricity, communication, project planning, water flow, road construction, and so on.